Multicentred randomised controlled trial of an augmented exercise referral scheme using web-based behavioural support in individuals with metabolic, musculoskeletal and mental health conditions: protocol for the e-coachER trial. Issue 9 (21st September 2018) - Ingram, Wendy; Webb, Douglas; Taylor, Rod S; Anokye, Nana; Yardley, Lucy; Jolly, Kate; Mutrie, Nanette; Campbell, John L; Dean, Sarah Gerard; Greaves, Colin; Steele, Mary; Lambert, Jeffrey D; et al.
Abstract : Introduction: Physical activity is recommended for improving health among people with common chronic conditions such as obesity, diabetes, hypertension, osteoarthritis and low mood. One approach to promote physical activity is via primary care exercise referral schemes (ERS). However, there is limited support for the effectiveness of ERS for increasing long-term physical activity and additional interventions are needed to help patients overcome barriers to ERS uptake and adherence. This study aims to determine whether augmenting usual ERS with web-based behavioural support, based on the LifeGuide platform, will increase long-term physical activity for patients with chronic physical and mental health conditions, and is cost-effective. Methods and analysis: A multicentre parallel two-group randomised controlled trial with 1:1 individual allocation to usual ERS alone (control) or usual ERS plus web-based behavioural support (intervention) with parallel economic and mixed methods process evaluations. Participants are low active adults with obesity, diabetes, hypertension, osteoarthritis or a history of depression, referred to an ERS from primary care in the UK. The primary outcome measure is the number of minutes of moderate-to-vigorous physical activity (MVPA) in ≥10 min bouts measured by accelerometer over 1 week at 12 months. We plan to recruit 413 participants, with 88% power at a two-sided alpha of 5%, assuming 20% attrition, to demonstrate a between-group difference of 36–39 min of MVPA per week at 12 months. An improvement of this magnitude represents an important change in physical activity, particularly for inactive participants with chronic conditions. Ethics and dissemination: Approved by North West Preston NHS Research Ethics Committee (15/NW/0347). Dissemination will include publication of findings for the stated outcomes, parallel process evaluation and economic evaluation in peer-reviewed journals. Results will be disseminated to ERS services, primary healthcare providers and trial participants. Trial registration number: ISRCTN15644451 ; Pre-results.